The prognostic role of mitosis index, stage and grade of endometrial cancer in Dr. Soetomo General Academic Hospital Surabaya, Indonesia, in 2018-2020 - Umi Choviva, Farida; Sandhika, Willy; Mulawardhana, Pungky (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS 1. Mitotic index and grade are prognostic factors for endometrial cancer, but both are independent.2. Stage and mitotic index associated with cell proliferation affect the prognosis of endometrial cancer.   ABSTRACT Objective: This study aimed to analyze the correlation between the mitotic index and the stage and grade of endometrial cancer. Materials and Methods: We collected pathology reports of endometrial cancer from the Pathology Laboratory at Dr. Soetomo General Hospital in Surabaya, Indonesia, covering cases diagnosed between 2018 and 2020. A total of 106 cases of endometrial cancer were included in this study. For each case, detailed records of the cancer stage, grade, and mitotic index were recorded. The mitotic index, an indicator of cell proliferation, was quantified, and its correlation with cancer stage and grade was assessed. To determine the strength and direction of these relationships, we performed a Spearman rank correlation statistical analysis for non-parametric data. Results: Our findings indicated a significant positive correlation between the mitotic index and the stage of endometrial cancer. An increase in the mitotic index, reflecting a higher proliferation rate of cancer cells, was associated with a more advanced cancer stage, suggesting that the mitotic index could potentially serve as a prognostic marker for assessing tumor progression in endometrial cancer. However, our analysis revealed no significant correlation between the mitotic index and the histological grade of endometrial cancer, implying that the grade, which typically reflects the differentiation status and morphological characteristics of the tumor cells, is independent of the proliferation rate as measured by the mitotic index. Conclusion: The mitotic index is positively correlated with the stage of endometrial cancer but does not show a correlation with the histological grade. These findings highlight the potential use of the mitotic index in staging endometrial cancer.